Dampak Budaya Organisasi Terhadap Retensi Karyawan Di Mikibal Caffe, Lubuk Begalung, Padang - Jihan Atifa; Adiprana Mahendra; Ilhamsyah Putra; Laras Dwi Safitri; Vivi Nila Sari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
A strong and positive organizational culture is believed to create a supportive work environment, increase job satisfaction, and strengthen employee loyalty, thereby reducing turnover rates. This research uses a quantitative approach, with data collected through questionnaires distributed to employees of Mikibal Café. The data were analyzed using statistical methods to determine the effect of organizational culture on employee retention. The results indicate that organizational culture has a significant influence on employee retention, meaning that the better the implementation of organizational cultural values such as teamwork, effective communication, and supportive leadership, the higher the employees’ intention to remain with the organization. This study is expected to provide practical implications for the management of Mikibal Café in developing human resource management strategies focused on strengthening organizational culture to improve employee retention and achieve sustainable organizational performance.